WEIGHT DIARY: AN ANDROID APPLICATION MONITORING DAILY ROUTINE FOR BODY WEIGHT PREDICTION THROUGH LIFESTYLE MINING - Gulay, Crisanto F; Sapin, Sherwin B; Echalar, Loyd S (Journal of Agriculture and Technology Management, 2021)
Monitoring daily dietary intake and weight is relevant to having normal nutritional status. Being underweight, overweight, or obese primarily results from the imbalance of dietary intake and physical activity. Proper monitoring of daily lifestyle by maintaining healthy weight through balanced dietary intake and physical activity can aid in improving the nutritional status of an individual. With this, an application was developed which could monitor the daily dietary intake and (daily/weekly) weight of an individual, and could provide recommendations in achieving the recommended body weight. The project lifestyle mining was accomplished by using the Agile Methodology. The developed application evaluated using the ISO 25000 quality standards, and results showed that it could be utilized in monitoring the dietary intake and body weight, and further improves the user’s nutritional status. It is suggested that the application must be used for a longer period to further determine its affectivity in improving an individual’s nutritional status. More information about the user which can contribute to nutritional status can also be considered to be included in the system.